Utilization of Liquid Smoke from Oil Palm Empty Fruit Bunches on Raw Rubber Processing - Asmawit, Asmawit; Hidayati, Hidayati; Supriyatna, Nana (Biopropal Industri, 2011)
Research utilization of liquid smoke from oil palm empty fruit bunches of raw rubber has been made to utilize solid waste from industrial processing of oil palm empty fruit bunches of oil palm so that it becomes economically valuable products. This research has been done by pyrolysis of oil palm empty fruit bunches at a temperature of 400oC for 5, 6, 7 and 8 hours. The results show that the pyrolysis liquid smoke oil palm empty fruit bunches for 8 hours give a high concentration of phenol and acetic acid, respectively 5% and 0.454%. Liquid smoke that has been obtained is used as a coagulant in raw rubber plantation crops of the people residing in the village of Ambawang, Kubu Raya District, West Kalimantan. Results of treatment of liquid smoke on raw rubberÂ  show that the rubber products that have been frozen and dried are superior in terms of color, smell and drying time compared with the treatment of formic acid and water battery which has been added so far on raw rubber by the local rubber farmers.